Collision‐Induced Absorption of CH4‐CO2 and H2‐CO2 Complexes and Their Effect on the Ancient Martian Atmosphere. Issue 12 (19th December 2020) - Godin, Paul J.; Ramirez, Ramses M.; Campbell, Charissa L.; Wizenberg, Tyler; Nguyen, Tue Giang; Strong, Kimberly; Moores, John E.
Abstract: Experimental measurements of collision‐induced absorption (CIA) cross sections for CO2 ‐H2 and CO2 ‐CH4 complexes were performed using Fourier transform spectroscopy over a spectral range of 150–475 cm −1 and a temperature range of 200–300 K. These experimentally derived CIA cross sections agree with the spectral range of the calculation by Wordsworth et al. (2017) however, the amplitude is half of what was predicted. Furthermore, the CIA cross sections reported here agree with those measured by Turbet et al. (2019, 2019). Additionally, radiative transfer calculations of the early Mars atmosphere were performed, and showed that CO2 ‐CH4 CIA would require surface pressure greater than 3 bar for a 10% methane atmosphere to achieve 273 K at the surface. For CO2 ‐H2, liquid water is possible with 5% hydrogen and less than 2 bar of surface pressure. Plain Language Summary: New temperature‐dependent infrared absorption properties of CO2 ‐H2 and CO2 ‐CH4 gas mixtures were experimentally tested against a theoretical prediction. Ultimately, we find that the strength of the absorption was half of what was predicted. Absorption between CO2 ‐H2 and CO2 ‐CH4 was proposed as a way to increase the greenhouse gas effect on ancient Mars, so that Mars would be warm enough to have liquid water on the surface. Ancient Mars climate was simulated using the new gas mixture absorption properties. Since the experimental absorption was weaker than predicted, we find that CO2 ‐CH4 is insufficient in warming ancient Mars, but CO2 ‐H2 remains a possibility. Key Points: First experimental measurements of CO2 ‐H2 and CO2 ‐CH4 CIA cross sections at multiple temperatures Radiative transfer calculations of the early Mars atmosphere were performed using the newly acquired CIA cross sections Surface temperatures above 273 K can be reached if surface pressures exceed 3 bar for 10% CH4 or 2 bar for a 5% H2 atmosphere